Evaluation of open reduction and internal fixation of displaced intra-articular fracture of calcaneum- A short term study - Jha, Ranjib Kumar; Thapa, Santosh (Birat Journal of Health Sciences, 2020)
Introduction: Management of displaced intraarticular fracture of calcaneum is controversial. Non-operative management often have unsatisfactory result due to subtalar arthritis and abnormal foot morphology. Objective: The objective of the study was to evaluate clinical and radiological outcome of patients with displaced intra-articular fracture of calcaneum treated by open reduction and internal fixation(ORIF) with plates and screws through extensile lateral approach. Methodology: This was prospective clinical study conducted in Nobel Medical College between November 2016 to December 2019. The patients were treated by ORIF with calcaneal plates and screws through extensile lateral approach. Patients were followed up for minimal one year. Patients were evaluated clinically by using AOFAS hind foot score and radiologically by measuring Bohler’s and Gissane angle and calcaneal height and width. Results: Out of total 26 cases, fifteen were sander’s type II, eight were type III and three were type IV. The mean age of patients was 33.92 years. The mean delay of surgery due to swelling was 8.65±1.95 days. The averagefollow-up period was 17 months. The mean AOFAS hind foot score was85.08±7.67. Tenpatients (38.46%) had excellent, twelve patients(48.61%) had good and four patients(15.38%) had fair outcome.There were significant association between improvement in Bohler’s and Gissane angle and functional outcome measured by AOFAS hind foot score. Conclusion : Open reduction and internal fixation of displaced intraarticular fracture of calcaneum with calcaneal plates and screws through extensile lateral approach produce good clinical and radiological result.